Analisis Minat Belajar Siswa Ma Al-Mubarok Melalui Pendekatan Saintifik Berbantuan Aplikasi Geogebra Pada Materi Statistika Dasar - Novie Suci Rahmawati; Titin Kurnia Bungsu; Irna Daulatina Islamiah; Wahyu Setiawan (Journal on Education, 2019)
This study aims to analyze student learning interest through geogebra application. The research method uses descriptive qualitative with a population of all MA students in West Bandung Regency. The samples used were 29th grade students of Mia Al-Mubarok as many as 29 students in basic statistical material. The instrument used is the Learning Interest Scale with 20 statements that have positive and negative responses about learning using the geogebra application. The learning interest scale is used to look for responses from respondents to the interest in learning from high school / MA students in statistical material whose learning uses the scientific approach using geogebra applications. The results of this study indicate that students' learning interest in statistical material with geogebra application media showed positive results with the average response showing a strong category with a percentage of 63.27%. The average is obtained from data on each indicator of student learning interest.